Evaluating the Performance of Two Rapid Immunochromatographic Techniques for Detecting Carbapenemase in Carbapenem-Resistant Enterobacterales Clinical Isolates - Liu P; Qin M; Zhao C; Yi S; Ye M; Liao K; Deng J; Chen Y (Infection and Drug Resistance)
Pingjuan Liu,1,* Mengling Qin,2,* Chenfeng Zhao,1,* Siting Yi,3 Mengmin Ye,3 Kang Liao,1 Jiankai Deng,1 Yili Chen1 1Department of Laboratory Medicine, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, 510080, People’s Republic of China; 2Department of Laboratory Medicine, Hainan West Central Hospital, Hainan, 571700, People’s Republic of China; 3Department of Laboratory Medicine, The East Division of The First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, Guangdong, 510080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yili Chen; Jiankai Deng, Department of Laboratory Medicine, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, 510080, People’s Republic of China, Email chenyli3@mail.sysu.edu.cn; dengjk0417@126.comIntroduction: The rapid and accurate identification of carbapenemases in Enterobacterales isolates is of paramount importance for the selection of effective antibiotics and the control of hospital-acquired infections.Methods: This study aimed to evaluate the performance of two immunochromatographic methods, NG-Test Carba 5 (Carba 5) and Goldstream Carbapenem-resistant K.N.I.V.O. Detection K-Set (K-Set) for detecting five major carbapenemase (KPC, NDM, IMP, OXA-48-like, and VIM). Carbapenemase genes were confirmed by PCR.Results: In this study, a total of 245 carbapenem-resistant Enterobacterales (CRE) isolates were encompassed, with an overwhelming 96.7% of these strains exhibiting the ability to produce carbapenemase. A total of 58.2% of Klebsiella pneumoniae strains that produce KPC carbapenemase were the most prevalent among carbapenem-resistant Enterobacteriaceae (CRE). NDM-producing Klebsiella pneumoniae accounted for 30.4%. Importantly, NDM-type carbapenemase emerges as the predominant form in Escherichia coli and Enterobacter cloacae strains, accounting for 46 (93.9%) and 20 (83.3%) cases, respectively. The performance of the two methods in carbapenemase detection has demonstrated remarkable outcomes, exhibiting overall specificity and sensitivity exceeding 99%. Specifically, the K-Set accurately detected a unique KPC-carbapenemase in K. pneumoniae, whereas Carba 5 was unable to identify it. This was due to the presence of a novel blaKPC gene, which harbored a specific point mutation (A to G) at nucleotide position 787, differentiating it from the blaKPC-33 gene.Conclusion: These two methods, characterized by their simplicity, rapidity, and accuracy, are ideally suited for detecting carbapenemases in routine microbiology laboratories. They serve as a vital foundation for the rational selection of antibiotics in clinical practice.Keywords: carbapenem-resistant Enterobacterales, CRE, carbapenemase gene, rapid immunochromatographic